Effect of difficulty of task on throwing performance and coping strategies in team handball - van den Tillaar, Roland; Hope, Christopher (Frontiers in Sports and Active Living, 2023)
In this study the effect of level of opposition on throwing performance and coping strategies in the jump throw was examined in elite, amateur, and adolescent players in team handball. Twenty four participants consisting of 13 female elite junior handball players (age: 15.5 ± 0.7 years; height: 1.72 ± 0.07 m; body mass: 64.2 ± 7.0 kg; years of handball experience: 8.4 ± 1.76 years) and 11 senior recreational female handball players (age: 19.5 ± 1.04 years; height: 1.68 ± 0.08 m; body mass: 65.2 ± 9.3 kg; years of handball experience: 11 ± 2.61 years) performed ten jump throws under four conditions: 1) without opposition; 2) with a passive opponent; 3) with an opponent moving sideways; and 4) with a defender who was instructed to be unpredictable without physical contact with the thrower. Ball velocity and accuracy were measured for every throw together with answering a questionnaire consisting of 18 questions after each condition to investigate if coping strategies changed with increasing difficulty of task and if this was different for playing level. The main findings were that ball velocity and accuracy decreased when opposition was introduced, but with no differences when the opposition moved only sideways or unpredictably (forwards and/or sideways), similarly for both groups. Furthermore, the level had no influence on the coping strategies or a relationship with either of these coping strategies, but the avoidance coping strategy scored lower than the other two categories for both groups. It was concluded that level of opposition had a negative effect on throwing velocity and accuracy in elite junior and recreational level senior players which was probably caused by the change of given attention to one target (overcome opponent), which leaves less available for others (throwing velocity and accuracy). Furthermore, coping strategies did not change or have any correlation with throwing performance, indicating that these strategies seem to be influenced by trait and that most players mainly used problem- and emotional-focused coping strategies and less avoidance strategies when dealing with the level of opposition.